Utility of activated partial thromboplastin time waveform analysis for identification of sepsis and overt disseminated intravascular coagulation in patients admitted to a surgical intensive care unit - Dempfle, Carl-Erik H; Lorenz, Stephan; Smolinski, Mathias; Wurst, Michael; West, Steve; Houdijk, Wim P M; Quintel, Michael; Borggrefe, Martin (Critical care medicine, 2004)
An abnormality of the optical transmission waveform obtained during measurement of the activated partial thromboplastin time (aPTT) has been described in association with overt disseminated intravascular coagulation. This abnormality, a biphasic waveform, is caused by the in vitro formation of Ca2+-induced complexes between very low density lipoprotein and C-reactive protein. We have evaluated the diagnostic utility of aPTT waveform analysis for identifying patients with overt disseminated intravascular coagulation and sepsis. Observational study investigating the predictive value of biphasic waveform for the diagnosis of sepsis and overt disseminated intravascular coagulation. Surgical intensive care unit of a university hospital. We studied 331 consecutive patients admitted to the intensive care unit during a period of 6 months. Laboratory analyses, including prothrombin time, aPTT, aPTT waveform analysis, fibrinogen, D-dimer antigen, and platelet count. At the most sensitive threshold value of the waveform variable for detection of the biphasic waveform (slope_1 = -0.05 %T/sec), this abnormality was detected in 54 of 331 patients (16.3%) at admission and 95 of 331 patients (28.7%) during the entire course of intensive care unit treatment. At this threshold, 59.3% of patients with a biphasic waveform on admission and 45.3% with a biphasic waveform during the total intensive care unit course were diagnosed with sepsis. Depending on the threshold value of slope_1, the sensitivity of aPTT waveform analysis for detection of sepsis varied between 22% and 55% at admission and between 48% and 74% during the entire intensive care unit stay. The specificity for sepsis varied between 92% and 98% and between 81% and 94%, for admission and total intensive care unit course, respectively. Biphasic waveform showed a comparable specificity for the diagnosis of overt disseminated intravascular coagulation, albeit at a lower sensitivity. As an adjunct to routine coagulation testing in intensive care unit patients, aPTT waveform analysis is an elegant means for the rapid and highly specific identification of patients with sepsis.